Exploring levels and correlates of health literacy in Arabic and Vietnamese immigrant patients with cancer and their English-speaking counterparts in Australia: a cross-sectional study protocol. Issue 7 (1st August 2018) - Gerges, Martha; Smith, Allan Ben; Durcinoska, Ivana; Yan, Henry; Girgis, Afaf
Abstract : Introduction: For immigrants diagnosed with cancer, the stress of a cancer diagnosis and treatment can be amplified by unfamiliarity with the health system, lack of culturally and linguistically appropriate information, and inability to communicate efficiently and accurately with the treating team. Lower levels of health literacy may be one factor underlying poorer outcomes among immigrant patients with cancer, but there have been few studies exploring this issue to date. This study aims to investigate the levels and correlates of health literacy in two immigrant populations affected by cancer and their English-speaking counterparts. Methods and analysis: Levels and correlates of health and eHealth literacy will be evaluated using a cross-sectional self-report questionnaire. Eligible, English, Arabic and Vietnamese patients with cancer and survivors (n=50 of each language group) will be invited to complete a questionnaire in their preferred language containing the Health Literacy Questionnaire, the eHealth Literacy Scale and study-specific questions assessing potential correlates of poor health literacy, including gender, age, education level, acculturation into Australian society and number of chronic illnesses. Multivariable logistic regression will be used to identify potential approaches to support effective communication with healthcare providers and preferred methods for assessing patient-reported outcomes (PROs) to support culturally appropriate cancer care. The outcomes of this study will be used to better meet the needs of immigrant populations, including the tailoring of interventions appropriate to different health literacy levels. Outcomes will also inform strategies for PRO assessment to inform unmet needs and to address Australian healthcare system challenges to meet the needs of immigrant populations. Ethics and dissemination: The study was reviewed and approved by the Human Research Ethics Committee of South Western Sydney Local Health District (approval number: HREC/16/LPOOL/650). Results from the study will aim to be published at international conferences and in peer-reviewed journals.